Comparing four training modalities on body composition, cardiorespiratory fitness and cardiovascular responses in sedentary young men: a randomized trial - Weihua Zheng; Shuai Han; Shunzhe Piao; Runrong Tang; Hansen Li; Weipeng Liu; Yang Cao (BMC Sports Science, Medicine and Rehabilitation, 2026)
Abstract Background Although high-intensity interval training (HIIT), high-intensity continuous training (HICT), moderate-intensity interval training (MIIT), and moderate-intensity continuous training (MICT) have all been shown to improve health outcomes, few studies have compared these four modalities within the same framework. Therefore, this study aimed to compare the effects of 8 weeks of HIIT, HICT, MIIT, and MICT on body composition, cardiorespiratory fitness, and cardiovascular responses in sedentary young men. We hypothesized that high-intensity training would produce greater improvements than moderate-intensity training. Methods Forty sedentary men aged 20-28 years were randomized to the HIIT, HICT, MIIT, or MICT group, of whom 38 completed the intervention, corresponding to an attrition rate of 5%. Participants completed three approximately 45-minute training sessions per week for 8 weeks, with exercise intensity prescribed at 77%-95% of maximal heart rate (HRmax) and a rating of perceived exertion (RPE) of 14-17 for the HICT and HIIT groups and at 64%-76% HRmax and an RPE of 12-13 for the MICT and MIIT groups, while exercise duration was matched across groups at 120 seconds per movement. The primary outcomes were VO2peak and cardiovascular responses, including resting and peak-exercise heart rate, systolic and diastolic blood pressure, and rate-pressure product. Secondary outcomes included total exercise duration to volitional exhaustion during the Bruce graded exercise test (Bruce test duration) and body-composition measures. Group-by-time interactions were examined using linear mixed-effects models, followed, where appropriate, by Bonferroni-adjusted post hoc comparisons. Results Significant group-by-time interactions were observed for VO2peak (P = 0.040, η2 = 0.21), Bruce test duration (P = 0.016, η2 = 0.26), resting systolic blood pressure (P < 0.001, η2 = 0.44), resting rate–pressure product (P < 0.001, η2 = 0.40), peak-exercise systolic blood pressure (P = 0.001, η2 = 0.36), and peak-exercise rate–pressure product (P < 0.001, η2 = 0.42). In contrast, the interactions were nonsignificant for resting heart rate (P = 0.064, η2 = 0.21), resting diastolic blood pressure (P = 0.615, η2 = 0.05), peak-exercise heart rate (P = 0.078, η2 = 0.18), and peak-exercise diastolic blood pressure (P = 0.220, η2 = 0.12). Bonferroni-adjusted comparisons showed a greater increase in VO2peak with HIIT than with MIIT (MD = 1.11 mL·kg-1·min-1; 95% CI [0.20, 2.01], g = 1.54; P < 0.01), whereas no adjusted between-group differences were detected for Bruce test duration. The largest differences in cardiovascular responses were observed between HICT and MIIT for resting systolic blood pressure (MD= -4.95 mmHg; 95% CI [-7.65, -2.25], g = -1.70), resting rate–pressure product (MD= -0.80 mmHg·bpm; 95% CI [-1.18, -0.42], g = -1.61), and peak-exercise systolic blood pressure (MD= -6.07 mmHg; 95% CI [-10.38, -1.76], g = -1.94), whereas the largest difference in peak-exercise rate–pressure product was observed between HIIT and MIIT (MD= -0.77 mmHg·bpm, 95% CI [-1.26, -0.28], g = -1.79). No group-by-time interactions were detected for body weight (P = 0.985), fat mass (P = 0.950), fat-free mass (P = 0.977), body mass index (P = 0.924), or visceral adipose tissue (P = 0.273). Conclusions These preliminary findings suggest outcome-specific differences among the training protocols. HIIT improved VO2peak more than MIIT, while high-intensity protocols showed greater improvements in selected cardiovascular responses. No adjusted between-group differences were detected for Bruce test duration, and no differential effects were observed for body composition. Larger controlled trials are needed to confirm these findings. Trial registration Chinese Clinical Trial Registry ChiCTR2500106395. Registered 23 July 2025.